Exploring insights of hydroxychloroquine, a controversial drug in Covid-19: An update. (May 2021) - Joshi, Gaurav; Thakur, Shikha; Mayank,; Poduri, Ramarao
Abstract: The review summarizes chloroquine (CQ) and its safer derivative hydroxychloroquine (HCQ) and its utility in Covid-19. Recently this well-established drug made its way back to the headlines during the SARS-CoV-2 pandemic. This led to an upsurge in the scientific arena with multiple research and review articles along with expert opinions and commentaries. The HCQ has received mixed judgements so far about its efficacy to be used in Covid-19 patients in a limited trial conducted all across the Globe. The purpose of our article is to put forth the history, pharmacodynamics, and pharmacokinetics, along with the existing studies favouring and disapproving the role of HCQ in the treatment of Covid-19. We grouped HCQ use at three stages, this includes HCQ for i. prophylactic use by asymptomatic health workers or peoples at higher risk; ii. patients having mild symptoms; iii. patients with extreme symptoms. The review critically discusses the underlying plausible reasons and mechanisms exploring HCQ in prophylactic management or treatment of SARS-CoV-2. Furthermore, we have critically analysed the reported pharmacokinetic parameters and compiled the proponent, opponent, or neutral opinions on the use of HCQ in Covid-19. Authors discretion is to conduct more studies considering the optimal dosing regimen and pharmacokinetics assessment. Graphical abstract: Image 1 Highlights: The HCQ has received mixed judgements so far about its efficacy for Covid-19. Enough rationale exists to justify the efficacy and safety of HCQ in Covid-19. However, evidence of the effects is limited. A vital requirement of correlation between HCQ dose with its pharmacokinetics and its monitoring to ensure the safety and efficacy in the patients. Reported toxicities of ocular, gastrointestinal, and cardiac are associated with long-term use of HCQ and would not be of much relevance in treating Covid-19 disease, which is of concise duration.